African American pastors' perceptions of their congregants' mental health needs - Vassol, Elverta L. (Kansas State University, 2005)
The purpose of this study was to examine the factors that influenced African American pastor’s perceptions of mental health issues and to explore how those perceptions influenced the propensity of the pastor to counsel, consult, and or refer to mental health professionals. This study is divided into two parts. Part one examines the perceptions of the pastors and their beliefs about mental health. Part two concretized these perceptions by employing the Contextual Model of Family Stress as a guide for structuring the relationships between a pastor’s perception and their attitudes toward mental health issues. Data for this investigation were gathered from a sub-sample of African American pastors originally generated from a listing of churches throughout the country. Initially 300 locally based institutions were identified. A survey was mailed to the churches explaining the purpose and goals of the study. Nearly one-third of the pastors completed the sixty-one item questionnaire. Of those who returned the original questionnaires (102), nearly three-quarters were from African American pastors (73) all of whom were included in this study. There were four hypotheses developed for this exploratory investigation: they examined the pastor’s propensity to make mental health referrals; the tendency to spiritualize mental health issues; pastor’s lack of support for congregants with mental health problems; and the influence of mental health training on the willingness to refer to mental health professionals. None of the hypotheses were directly supported. The application and adaptation of the Contextual Model of Family Stress to how African American pastors perceived, utilized, and responded to mental health issues was explored via path analysis. Overall, the final model explained 39% of the variance in why pastors chose to make referrals to mental health professionals. The findings suggested that the African American pastors are concerned with the mental health of their congregants. Moreover, these pastors exhibited uncommon knowledge about mental health and displayed greater willingness to work with mental health professionals than originally believed. These findings reveal that African American pastors are in touch with their congregants on multiple plains—spiritual, soul, and body—three vital dimensions, according to church doctrines and beliefs.
Keywords: African American pastors; Mental health; Religion, Clergy (0319); Black Studies (0325)